Plasma triglyceride levels and central obesity predict the development of kidney injury in Chinese community older adults. (1st January 2019) - Cao, Yujie; Sun, Guangshan; Liu, Rui; Sun, Ao; Zhang, Qian; Li, Yang; Wang, Lele; Chao, Xiangli; Zhou, Xiaojie; Zhang, Sha; Chen, Ruping
Abstract: Objective: Despite the achievement of blood glucose, blood pressure targets, the risk for kidney injury remains high among older adults. This observational retrospective study investigated whether high TG or high WC contribute to this high residual risk for kidney injury. Methods: A total of 843 elderly from Dongli Community, Tianjin, China, we selected 666 individuals with a baseline estimated glomerular filtration rate (eGFR) ≥60 mL/min/1.73 m 2 and negative microalbuminuria completing a 3-year follow-up. At baseline, subjects were grouped according to the levels of TG and WC. The primary outcome was the incidence of kidney injury, defined as low eGFR (eGFR <60 mL/min/1.73 m 2 ) or reduced eGFR (eGFR reduced >25%) or UACR ≥30 mg/g. Results: Overall, 6.01% developed low eGFR, 11.11% reduced eGFR, 25.98% UACR ≥30 mg/g, and 3.45% low eGFR and UACR ≥30mg/g after 3-year follow-up. TG ≥1.7 mmol/L increased the risk of eGFR <60 mL/min/1.73 m 2 by 1.44-fold, of UACR ≥30 mg/g by 32%, and of developing both abnormality by 1.41-fold in model 1; further adjustment for potential confounders factors, the association is slightly weakened in model 2 and 3; WC (≥90 cm in men and ≥85 cm in women) were associated with a 1.68-fold higher risk of eGFR <60 mL/min/1.73 m 2 and a 1.43-fold risk of UACR ≥30 mg/g and a 1.89-fold risk of developing both abnormality in model 1. Further adjustment for potential confounders factors, the association is slightly weakened in model 2 and 3. Conclusions: In a population of Chinese community-dwelling older adults, high TG and central obesity were risk factors for the development of kidney injury over 3 years.